AFGHAN STUDENTS’ PURPOSES OF USING FACEBOOK AT MIRWAIS KHAN NIKA ZABUL INSTITUTE OF HIGHER EDUCATION, ZABUL, AFGHANISTAN - Himat, Abdul Nafi; Nazari, Habib Rahman (American International Journal of Social Science Research, 2021)
The aim of this study is to investigate the students’ purposes of using Facebook at Mirwais Khan Nika Zabul Institute of Higher Education, Qalat, Zabul province, Afghanistan. In this research, the quantitative research method was employed, and the data was collected from 115 students through a designed questionnaire. In addition, the respondents were selected through random sample. Additionally, the data was analyzed by implementing IBM 24 version of Statistical Package for the Social Sciences (SPSS), and found out the frequency and percentage of the items as well reported in a table. Moreover, the findings of this research reveal that learners use Facebook for several goals such as for socializing in order to be socialized in a society, getting social information, read news and for educational purposes, but they did not practice Facebook for the aims to pass their time, and share photos with their friends on the Facebook. JEL Classification Codes: A19, B10, B25, C10, C53